“THE TALE OF KIEU” – THE CHOICE OF VIETNAM VALUES - Phạm, Văn Hóa (TNU Journal of Science and Technology, 2024)
The purpose of this paper is to explain why an ordinary literary source has become the pinnacle of Vietnamese literature, elevated as a celebration of the national traditional cultural characteristics of Vietnam. This study focuses on the ideological transformation and adaptation of a scholar and a beauty novel into a Nom poetry. Based on national culture, the traditional six-eight-meter genre, and Nom script, a special literary work was born, reflecting many traditional cultural characteristics of Vietnam. The study shows how the transformation from a “normally average” literary work to a cultural characteristic symbol of Vietnamese national culture has played out. The article employs several methods such as analysis, synthesis, comparison, typological research, literature, and culture interdisciplinary methods, and a systematic approach. The paper sheds light on the adaptation of a literary work reaching the pinnacle of Vietnamese medieval written literature in the context of the regional and Vietnam‟s particular traditional culture through decoding the creative process of Nguyen Du‟s The Tale of Kieu - a symbol of Vietnamese national culture. The paper shows how a literary work has become a national literary peak and the image of The Tale of Kieu becomes a symbol of national consciousness, the spirit of cultural nationalization.